2010
DOI: 10.1016/j.resp.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

CO and NO pulmonary diffusing capacity during pregnancy: Safety and diagnostic potential

Abstract: This paper reviews the scientific evidence for the safety of carbon monoxide (CO) and nitric oxide (NO) inhalation to measure pulmonary diffusing capacity (DLCO and DLNO) in pregnant women and their fetuses. In eight earlier studies, 650 pregnant women had DLCO measurements performed at various times during pregnancy, with a minimum of two to four tests per session. Both pregnant subjects that were healthy and those with medical complications were tested. No study reported adverse maternal, fetal, or neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 113 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…There are no contraindications for DLNO and DLCO measurements other than patients who are unable to understand or collaborate to the procedure or unwilling to provide consent. Children aged <18 years are allowed to undergo DLNO and DLCO measurements, as are pregnant subjects [112].…”
Section: Contraindications To Dlno and Dlco Assessmentsmentioning
confidence: 99%
“…There are no contraindications for DLNO and DLCO measurements other than patients who are unable to understand or collaborate to the procedure or unwilling to provide consent. Children aged <18 years are allowed to undergo DLNO and DLCO measurements, as are pregnant subjects [112].…”
Section: Contraindications To Dlno and Dlco Assessmentsmentioning
confidence: 99%
“…Early after conception, major hemodynamic changes begin, reaching a peak during the 2 nd trimester. Some studies have shown a slight decrease in diffusing capacity of the lung for carbon monoxide (DLCO) [28]. Systemic vascular resistances tend to decrease while heart rate accelerates.…”
Section: Physiological Changes During Pregnancymentioning
confidence: 99%
“…Furthermore, all complaints of dyspnea in pregnant SSc patients should prompt an immediate evaluation for development or worsening of PAH. Assessing diffusion capacity using carbon monoxide is considered safe during pregnancy [ 29 ].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%